Use and Meaning of 'Market' in Inventory Valuation (Book). - Zeff, Stephen A.; Crichley, W. A. (The Accounting Review, 1963)
Reviews the book "Use and Meaning of Market in Inventory Valuation," by Gertrude Mulcahy.